Understanding and supporting parenting in parents seeking PTSD treatment: a qualitative study - Laurien Meijer; Kathleen Thomaes; Buket Karadeniz; Catrin Finkenauer (European Journal of Psychotraumatology)
Background: Parental post-traumatic stress disorder (PTSD) can impact parenting and child psychosocial wellbeing. Complementing trauma-focused psychotherapy with parenting interventions can thus have important preventive value. Understanding parents’ lived experiences is necessary to tailor such interventions to their needs.Objective: This study addressed the question: how can preventive parenting support be shaped to the needs of parents entering specialized psychotherapy for PTSD? To answer this question, we investigated parenting challenges, parent–child communication about PTSD, strengths, and social support experiences of parents with PTSD.Method: The sample included 14 parents seeking PTSD treatment at a tertiary mental healthcare institution, while parenting children aged 4-17. Data were collected using semi-structured interviews and analysed using reflexive thematic analysis.Results: On the one hand, parental dysregulation (e.g. exploding or shutting down) was an important challenge. On the other hand, parents’ attempts to remain regulated (e.g. through overcontrol and overprotectiveness) also affected family life. When talking to their child about PTSD, parents were guided by what they considered beneficial for the child to know. An important strength was that parents tried to remain attuned to the child’s needs, regardless of their own struggles. Parents also described experiences that could be understood as post-traumatic growth through parenting. Generally, parents experienced a lack of social support.Conclusion: Our findings illustrate that parents entering PTSD treatment are highly motivated to do what is best for their child. Based on parents’ lived experiences, preventive parenting interventions should address the impacts of both dysregulation and overcontrolling regulation attempts. Another important goal is reducing feelings of incompetence. Integrating the parenting role in psychotherapy for PTSD could also be beneficial. For example, setting parenting-related therapy goals can be motivating. Furthermore, parent–child interactions can be a mirror that reflects the parents’ inner state: considering these interactions can help recognize changes in symptomatology.